2021
DOI: 10.3389/fphar.2021.671835
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in PTGS1 and NOS3 Genes Increase the Risk of Upper Gastrointestinal Bleeding: A Case–Control Study

Abstract: Objective: To assess the association between PTGS1 and NOS3 variant alleles and the risk to develop upper gastrointestinal bleeding (UGIB) secondary to complicated peptic disease.Methods: A case–control study was conducted in a Brazilian complex hospital from July 2016 to March 2020. Case: Patients with UGIB diagnosis. Control: Patients admitted for surgery not related to gastrointestinal disorders. Variables: UGIB (outcome), genetic variants in PTGS1 and NOS3 genes (independent), and sex, age, schooling, ethn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Notably, the alleles of the PTGS1 and ADRA2A genes, associated with AR and/or high AA-induced aggregation in our study, correlated with a reduced risk of complications from the gastrointestinal tract when taking aspirin in other studies [ 61 , 62 , 63 ]. This may indicate a role in stimulating platelet activity in carriers of these alleles.…”
Section: Discussionsupporting
confidence: 64%
“…Notably, the alleles of the PTGS1 and ADRA2A genes, associated with AR and/or high AA-induced aggregation in our study, correlated with a reduced risk of complications from the gastrointestinal tract when taking aspirin in other studies [ 61 , 62 , 63 ]. This may indicate a role in stimulating platelet activity in carriers of these alleles.…”
Section: Discussionsupporting
confidence: 64%
“…The inclusion and exclusion criteria for the participants are described in detail in our three previous studies (4,10,11).…”
Section: Definition Of Cases and Control Participantsmentioning
confidence: 99%
“…One hypothesis for idiosyncratic responses to the use of NSAIDs and LDA is the presence of variants in genes involved in the drug metabolism of these drugs or in physiological functions in the gastrointestinal tract system and platelet aggregation cascade (3). In a previous study we evaluated six variants in PTGS1 and NOS3 genes and an increased magnitude of UGIB risk was observed in NSAIDs and LDA users (4). In order to continue this investigation, we identified other genetic variants potentially involved in the risk of gastric injury and UGIB and the *2 (Arg144Cys, rs1799853) and *3 alleles (Ile359Leu, rs10587910) of CYP2C9 gene stand out (3).…”
Section: Introductionmentioning
confidence: 99%
“…Both participants were recruited from the same hospital complex and the inclusion and exclusion criteria for the participants of case and control groups are described in detail in our two previous studies [6,13].…”
Section: Participantsmentioning
confidence: 99%
“…In our previous study, we evaluated in the Brazilian population the influence of rs2070744 and rs1799983 variants on the risk of upper gastrointestinal bleeding (UGIB) [6], a potential adverse drug reaction associated with high mortality, hospital readmissions, and the need for surgical intervention [7]. When the subgroups of LDA and NSAIDs users were considered, carriers of the variant alleles of rs2070744 and rs1799983 had a higher risk of developing UGIB [6], corroborating with a recent case-control study conducted with the Spanish population that also identified an increased risk of UGIB in LDA users carrying the variant allele of rs1799983 [8].…”
Section: Introductionmentioning
confidence: 99%